The Relationship Between Wrist Flexion And Leg Muscle Explosive Power Against Volleyball Smash Ability - Sistiasih, Vera Septi; Nurrohman, Dwi; Rumpoko, Satrio Sakti; Sholeh, Muchammad (Journal Coaching Education Sports, 2024)
This study aims to determine the relationship between wrist flexion and leg muscle explosive power on the volleyball smash ability of athletes at the Kusuma Bhirawa Ponorogo club. Smash ability is the most important technique in scoring points in volleyball, and in the Kusuma Bhirawa club there are still some athletes who can be said to be still lacking in smash ability, especially in the accuracy of the smash, in that case it can be influenced by factors that can support the athlete's smash ability. Therefore, the authors conducted this study which aimed to find out whether there is a relationship between wrist flexion and leg muscle explosive power on athletes' smash ability. The sample in this study used 15 athletes taken using the Purposive Sampling method. This study uses a type of correlation research, and data collection techniques in this study are carried out using test measurement instruments, including: 1. Vertical jump test, 2. Geniometer test, and 3. Smash Accuracy Test.